New and interesting records of birds in Wallacea - Bishop, K David (KUKILA, 1992)
During ten years (1981-1990) of birdwatching throughout the islands of Wallacea, I have accumulated a number of records which supplement and compliment information presented in White & Bruce's (1986) annotated checklist of the birds of this region and in subsequent publications. With the impending publication of a handguide to the birds of the region (Bishop & Coates in prep), it was considered important to document these observations prior to their inclusion in such a publication.